Reinforcing technology based on ECC material, reinforcing structure and building

By using expanded vitrified microspheres and shear studs in ECC materials, the interfacial bonding problem of ECC materials in the reinforced surface layer was solved, improving thermal insulation performance and construction efficiency, and achieving a comprehensive effect of seismic reinforcement and thermal insulation and energy saving.

CN119288241AInactive Publication Date: 2025-01-10CHANGCHUN INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411411702.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-01-10
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing ECC materials have interfacial bonding problems in the reinforcement layer, which prevents the reinforcement layer from working together with the wall and the thermal insulation performance from meeting building requirements, thus increasing the workload and cost.

Method used

Expanded vitrified microspheres are used as fine aggregate in ECC material, and shear studs are implanted into the building surface during construction. Combined with fiber mesh, multiple layers of ECC concrete are formed to enhance adhesion. Finally, a plastering treatment is performed to prevent thermal bridging.

Benefits of technology

It improves the thermal insulation and energy-saving performance of ECC materials, reduces construction steps and costs, and ensures the coordinated work of the reinforced surface layer and the building, achieving the effect of seismic reinforcement and thermal insulation and energy saving.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119288241A_ABST
    Figure CN119288241A_ABST
Patent Text Reader

Abstract

The invention discloses a reinforcing process based on an ECC material, a reinforcing structure and a building, and belongs to the technical field of building reinforcing, the reinforcing process comprises the following steps: after the surface of a to-be-reinforced building is subjected to pretreatment, a first layer of ECC material is sprayed, and a first ECC concrete layer is formed; the ECC material at least comprises expanded and vitrified microbeads as fine aggregate; paving fiber gridding cloth on the surface of the first ECC concrete layer, and uniformly pressing the fiber gridding cloth into the surface layer of the first ECC concrete layer; the surface of the fiber gridding cloth is hammered to the designated depth through shear-resistant studs with rubber gaskets, and the shear-resistant studs penetrate through the first ECC concrete layer to enter the building to be reinforced; and a second layer of ECC material continues to be sprayed, a second ECC concrete layer is formed, and plastering treatment is conducted. The heat preservation and energy saving effects can be improved, the construction steps are reduced, the construction cost is reduced, and good economic benefits are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building reinforcement, in particular to a reinforcement process based on ECC materials and a reinforced structure and a building. Background Art

[0002] For buildings, the envelope structure accounts for the largest proportion of the total operating energy consumption of the building, and the heat lost through the exterior wall in the envelope structure accounts for more than 70% of the entire envelope structure, and can even reach 90%, so the application of exterior wall energy-saving technology in the entire building is particularly important.

[0003] At present, the stock of existing buildings in my country is huge and it is impossible to carry out comprehensive renovation and new construction. Therefore, the reinforcement of existing buildings has gradually become a new direction for energy-saving transformation. The existing exterior wall reinforcement projects still mainly use traditional reinforced concrete as the reinforcement surface layer, which has a large self-weight, poor seismic performance, and poor thermal insulation performance. Therefore, it is necessary to use new wall reinforcement materials to make it have good seismic performance in actual buildings, greatly improve structural ductility, ensure building safety, and have better thermal performance characteristics to solve the current problems.

[0004] Engineered Cementitious Composites (ECC) are based on the design principles of micromechanics and have excellent mechanical properties, among which the ductility is remarkable. Compared with ordinary concrete, they have the characteristics of high strength, high toughness, high crack resistance and high damage resistance. They are effective in the field of seismic reinforcement. However, as a reinforced surface layer, there are always interface bonding problems in actual application, which makes it impossible for the reinforced surface layer and the wall to work well together and give full play to the material properties. At the same time, the thermal insulation performance cannot meet the building requirements. It is often necessary to increase thermal insulation measures to achieve green energy-saving goals, which leads to an increase in the amount of work and cost issues.

[0005] As an inorganic glassy mineral material, expanded vitrified microspheres have a certain particle strength due to surface vitrification, very stable physical and chemical properties, and excellent insulation, fire resistance, and sound absorption properties. They are widely used in energy-saving transformation. In the building materials industry, using vitrified microspheres as lightweight aggregates can improve the fluidity of mortar, reduce material shrinkage, improve product comprehensive performance, and reduce comprehensive production costs; however, due to the insufficient mechanical properties of expanded vitrified microspheres, they are difficult to be used in the reinforcement field. Summary of the invention

[0006] The object of the present invention is to provide a reinforcement process based on ECC materials to solve the problems raised in the above background technology.

[0007] To achieve the above objectives, the embodiments of the present invention provide the following technical solutions:

[0008] A reinforcement process based on ECC material, comprising the following steps:

[0009] After pre-treatment of the surface of the building to be reinforced, a first layer of ECC material is sprayed to form a first ECC concrete layer; the ECC material at least includes expanded vitrified microspheres as fine aggregate;

[0010] Lay a fiber mesh cloth on the surface of the first ECC concrete layer, and press the fiber mesh cloth evenly into the surface layer of the first ECC concrete layer;

[0011] On the surface of the fiber mesh cloth, shear studs with rubber gaskets are hammered to a specified depth so that the shear studs pass through the first ECC concrete layer and enter the interior of the building to be reinforced;

[0012] Continue to spray the second layer of ECC material to form the second ECC concrete layer, and then perform plastering treatment.

[0013] Preferably, the ECC material comprises the following components: Portland cement 550-650 kg / m 3 、Fly ash 650-750kg / m 3 , fine aggregate 320-420kg / m 3 , Polycarboxylic acid high efficiency water reducing agent 2-6kg / m 3 , water 300-400kg / m 3 , and mixed with polyvinyl alcohol fiber; the fine aggregate includes quartz sand and expanded vitrified microspheres.

[0014] Preferably, the volume content of the polyvinyl alcohol fiber is 1%-3%.

[0015] Preferably, the particle size of the quartz sand is 40-80 mesh; the particle size of the expanded vitrified microspheres is 50-70 mesh.

[0016] Preferably, in the fine aggregate, the volume proportion of expanded vitrified microspheres is 40%-60%.

[0017] Preferably, the fiber mesh cloth is a basalt fiber woven mesh.

[0018] Preferably, the thickness of the first ECC concrete layer is 8-12 mm.

[0019] Preferably, the thickness of the second ECC concrete layer is 10-15 mm.

[0020] Another object of the present invention is to provide a reinforced structure obtained through the above-mentioned ECC material-based reinforcement process.

[0021] Another object of the present invention is to provide a building comprising the above-mentioned reinforcement structure.

[0022] The reinforcement process based on ECC materials provided by the present invention can improve the thermal insulation and energy-saving performance of ECC materials by using expanded vitrified microspheres as fine aggregate to replace part of the quartz sand in the ECC materials while ensuring that the mechanical properties of the ECC materials are not greatly lost. At the same time, shear studs implanted on the surface of the building are used during the construction process to ensure the coordinated work of the reinforced surface layer and the building to be reinforced, so as to give full play to the material properties. Finally, thermal insulation treatment (plastering treatment) is performed on the surface after reinforcement to prevent the cold and hot bridge phenomenon caused by the shear studs. After meeting the reinforcement requirements of the entire building, the thermal insulation and energy-saving effects are improved, the construction steps are reduced, the construction cost is reduced, and good economic benefits are achieved. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 A three-dimensional schematic diagram of a reinforcement structure provided by an embodiment of the present invention;

[0024] Figure 2 A cross-sectional view of a reinforcement structure provided by an embodiment of the present invention;

[0025] Figure 3 A schematic structural diagram of a shear stud with a rubber gasket provided in an embodiment of the present invention;

[0026] Figure 4 This is a diagram showing the results of a compression test of an embodiment of the present invention;

[0027] Figure 5 This is a diagram showing the results of a splitting tensile test of an embodiment of the present invention;

[0028] Figure 6 This is a graph showing the test results of thermal conductivity of an embodiment of the present invention;

[0029] In the figure: 1-wall to be reinforced, 2-first ECC concrete layer, 3-fiber mesh cloth, 4-rubber gasket, 5-shear studs, 6-second ECC concrete layer. DETAILED DESCRIPTION

[0030] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0031] The embodiment of the present invention provides a composite reinforcement material having both seismic reinforcement and thermal insulation and energy-saving effects for use in the reinforcement of old existing buildings, thereby achieving the goal of lightweight, high efficiency and energy-saving transformation, and can solve the shortcomings of the ECC material surface layer in the prior art, such as poor thermal insulation performance, large dead weight, and waste of material performance.

[0032] Specifically, Figure 1-Figure 3 As shown, in one embodiment of the present invention, a reinforcement process based on ECC material is provided, which includes the following steps:

[0033] S1, after pre-treating the surface of the building to be reinforced, spraying the first layer of ECC material to form a first ECC concrete layer 2; the ECC material at least includes expanded vitrified microspheres as fine aggregate;

[0034] S2, laying a fiber mesh cloth 3 on the surface of the first ECC concrete layer 2, and evenly pressing the fiber mesh cloth 3 into the surface layer of the first ECC concrete layer 2;

[0035] S3, hammering the shear studs 5 with rubber gaskets 4 to a specified depth on the surface of the fiber mesh cloth 3, so that the shear studs 5 pass through the first ECC concrete layer 2 and enter the interior of the building to be reinforced;

[0036] S4, continue spraying the second layer of ECC material to form a second ECC concrete layer 6, and perform plastering treatment to obtain a reinforced structure.

[0037] In practical applications, the steps of pre-treating the surface of the building to be reinforced may specifically include: removing old mortar, wetting the surface of the building to be reinforced with water, and drilling holes at fixed positions according to the specifications of the shear bolts 5 and protecting the holes with protective sleeves.

[0038] In a preferred embodiment of the present invention, the ECC material comprises the following components: Portland cement 550-650 kg / m 3 、Fly ash 650-750kg / m 3 , fine aggregate 320-420kg / m 3 , Polycarboxylic acid high efficiency water reducing agent 2-6kg / m 3 , water 300-400kg / m 3 , and mixed with polyvinyl alcohol (PVA) fibers; fine aggregates include quartz sand and expanded vitrified microspheres.

[0039] Specifically, the polyvinyl alcohol fiber can adopt commercially available PVA domestic short-cut fibers; the silicate cement can adopt commercially available PO42.5 silicate cement; the fly ash can adopt commercially available Class I fly ash; and the polycarboxylic acid high-efficiency water-reducing agent, quartz sand and expanded vitrified microspheres can also adopt commercially available products.

[0040] In a preferred embodiment of the present invention, the volume content of the polyvinyl alcohol fiber is 1%-3%, preferably 1.5%-2%.

[0041] In a preferred embodiment of the present invention, the particle size of the quartz sand is 40-80 mesh; the particle size of the expanded vitrified microspheres is 50-70 mesh.

[0042] In a preferred embodiment of the present invention, the volume proportion of the expanded vitrified microspheres in the fine aggregate is 40%-60%, preferably 50%.

[0043] In a preferred embodiment of the present invention, the fiber mesh cloth 3 is a basalt fiber woven mesh. The basalt fiber woven mesh has good alkali corrosion resistance, flexibility, etc., and is more economical than other fiber woven meshes. In reinforcement, it is intended to make up for the loss of tensile properties of the reinforced surface layer caused by aggregate replacement, thereby ensuring the overall mechanical properties of the reinforced material.

[0044] In a preferred embodiment of the present invention, the thickness of the first ECC concrete layer 2 is 8-12 mm; the thickness of the second ECC concrete layer 6 is 10-15 mm.

[0045] In the embodiment of the present invention, the rubber gasket 4 is used to enhance the adhesion between the fiber mesh cloth 3 and the first ECC concrete layer 2, thereby avoiding slippage and dislocation between the fiber mesh cloth 3 and the first ECC concrete layer 2, thereby affecting the reinforcement effect; the shear bolts 5 are used to enhance the effective bonding between the first ECC concrete layer 2 and the building to be reinforced, thereby ensuring better coordination between the first ECC concrete layer 2 and the building to be reinforced.

[0046] The following embodiments are some specific implementation cases and application cases of the present invention in practical applications, but are not limited thereto.

[0047] Embodiment 1: This embodiment provides a reinforcement process for a wall, which comprises the following steps:

[0048] (1) First, according to the following components: PO42.5 silicate cement 600kg / m 3 、Class I fly ash 700kg / m 3 , 40-80 mesh quartz sand 338.5kg / m 3 , 50-70 mesh expanded vitrified microspheres 31.7kg / m 3 , Polycarboxylic acid high efficiency water reducing agent 4kg / m 3 、Laboratory water 360kg / m 3, and polyvinyl alcohol fiber (volume dosage is 1.5%), weigh various raw materials, among which the fine aggregate is composed of quartz sand and expanded vitrified microspheres, and the volume ratio of the two is 1:1; then, pour the weighed polycarboxylic acid high-efficiency water-reducing agent into the water, stir evenly and set aside; reserve 1 / 3 of the cementitious material, pour the remaining cement, expanded vitrified microspheres, quartz sand, and fly ash into the mixing bucket and mix them, and dry stir for 2-4 minutes to mix the various materials evenly; then slowly pour the prepared aqueous solution into the mixing bucket, stir at a low speed for 3-5 minutes, and evenly add PVA fiber during the stirring process. After all the fibers are added, add the remaining 1 / 3 of the cementitious material and stir at a high speed for 3-5 minutes until the mixture in the mixer shows good fluidity and the short-cut fibers do not agglomerate, that is, the preparation is completed, and the ECC material is obtained.

[0049] (2) Pre-treat the surface of the wall 1 to be reinforced by removing old mortar, wet the surface of the wall 1 to be reinforced by watering, and at the same time, drill holes at fixed positions according to the specifications of the shear studs 5 and protect the holes with protective sleeves, and then spray the first layer of ECC material to form a first ECC concrete layer 2 with a thickness of 10 mm.

[0050] (3) Lay the fiber mesh cloth 3 on the surface of the first ECC concrete layer 2 and press the fiber mesh cloth 3 evenly into the surface layer of the first ECC concrete layer 2 .

[0051] (4) Remove the protective sleeve from the above-mentioned hole, and hammer the shear bolt 5 with the rubber gasket 4 to the specified depth on the surface of the fiber mesh cloth 3, so that the shear bolt 5 passes through the first ECC concrete layer 2 and enters the interior of the wall 1 to be reinforced; wherein, the shear bolt 5 is M12, the screw length is 100 mm, and the rubber gasket 4 is a circular rubber sheet with a diameter of 60 mm, which is convenient for combination with the bolt. The number of holes required for installing the shear bolt 5 is not less than 25 per square meter, and the height of the bolt end face from the wall surface must be greater than 10 mm.

[0052] (5) Continue spraying the second layer of ECC material to form a second ECC concrete layer 6 with a thickness of 12 mm, and perform surface treatment to obtain a reinforced structure.

[0053] Embodiment 2: This embodiment provides a reinforcement process for a wall, which comprises the following steps:

[0054] (1) First, according to the following components: PO42.5 silicate cement 550kg / m 3 、Class I fly ash 650kg / m 3 , fine aggregate 420kg / m 3 , Polycarboxylate high efficiency water reducing agent 2kg / m 3 、Laboratory water 400kg / m 3, and polyvinyl alcohol fiber (volume dosage is 1%), weigh various raw materials, among which the fine aggregate is composed of quartz sand and expanded vitrified microspheres, among which the volume of expanded vitrified microspheres accounts for 60%; then, pour the weighed polycarboxylic acid high-efficiency water-reducing agent into the water, stir evenly for use; reserve 1 / 3 of the cementitious material, pour the remaining cement, expanded vitrified microspheres, quartz sand, and fly ash into the mixing barrel and mix them, and dry stir for 2-4 minutes to mix the various materials evenly; then slowly pour the prepared aqueous solution into the mixing barrel, stir at a low speed for 3-5 minutes, and evenly add PVA fiber during the stirring process. After all the fibers are added, add the remaining 1 / 3 of the cementitious material and stir at a high speed for 3-5 minutes until the mixture in the mixer shows good fluidity and the short-cut fibers do not agglomerate, that is, the preparation is completed, and the ECC material is obtained.

[0055] (2) Pre-treat the surface of the wall 1 to be reinforced by removing old mortar and moistening the surface of the wall 1 with water. At the same time, holes are drilled at fixed positions according to the specifications of the shear studs 5 and the holes are protected with protective sleeves. Then, the first layer of ECC material is sprayed to form a first ECC concrete layer 2 with a thickness of 8 mm.

[0056] (3) Lay the fiber mesh cloth 3 on the surface of the first ECC concrete layer 2 and press the fiber mesh cloth 3 evenly into the surface layer of the first ECC concrete layer 2 .

[0057] (4) Remove the protective sleeve from the above-mentioned hole, and hammer the shear bolt 5 with the rubber gasket 4 to the specified depth on the surface of the fiber mesh cloth 3, so that the shear bolt 5 passes through the first ECC concrete layer 2 and enters the interior of the wall 1 to be reinforced; wherein, the shear bolt 5 is M12, the screw length is 100 mm, and the rubber gasket 4 is a circular rubber sheet with a diameter of 60 mm, which is convenient for combination with the bolt. The number of holes required for installing the shear bolt 5 is not less than 25 per square meter, and the height of the bolt end face from the wall surface must be greater than 10 mm.

[0058] (5) Continue spraying the second layer of ECC material to form a second ECC concrete layer 6 with a thickness of 10 mm, and perform surface treatment to obtain a reinforced structure.

[0059] Embodiment 3: This embodiment provides a reinforcement process for a wall, which comprises the following steps:

[0060] (1) First, according to the following components: PO42.5 silicate cement 650kg / m 3 、Class I fly ash 750kg / m 3 , fine aggregate 320kg / m 3 , Polycarboxylate high efficiency water reducing agent 6kg / m 3 、Laboratory water 300kg / m3 , and polyvinyl alcohol fiber (volume dosage is 3%), weigh various raw materials, among which the fine aggregate is composed of quartz sand and expanded vitrified microspheres, among which the volume of expanded vitrified microspheres accounts for 40%; then, pour the weighed polycarboxylic acid high-efficiency water-reducing agent into the water, stir evenly for use; reserve 1 / 3 of the cementitious material, pour the remaining cement, expanded vitrified microspheres, quartz sand, and fly ash into the mixing bucket and mix them, and dry stir for 2-4 minutes to mix the various materials evenly; then slowly pour the prepared aqueous solution into the mixing bucket, stir at a low speed for 3-5 minutes, and evenly add PVA fiber during the stirring process. After all the fibers are added, add the remaining 1 / 3 of the cementitious material and stir at a high speed for 3-5 minutes until the mixture in the mixer shows good fluidity and the short-cut fibers do not agglomerate, that is, the preparation is completed, and the ECC material is obtained.

[0061] (2) Pre-treat the surface of the wall 1 to be reinforced by removing old mortar, wet the surface of the wall 1 to be reinforced by watering, and at the same time, drill holes at fixed positions according to the specifications of the shear studs 5 and protect the holes with protective sleeves, and then spray the first layer of ECC material to form a first ECC concrete layer 2 with a thickness of 12 mm.

[0062] (3) Lay the fiber mesh cloth 3 on the surface of the first ECC concrete layer 2 and press the fiber mesh cloth 3 evenly into the surface layer of the first ECC concrete layer 2 .

[0063] (4) Remove the protective sleeve from the above-mentioned hole, and hammer the shear bolt 5 with the rubber gasket 4 to the specified depth on the surface of the fiber mesh cloth 3, so that the shear bolt 5 passes through the first ECC concrete layer 2 and enters the interior of the wall 1 to be reinforced; wherein, the shear bolt 5 is M12, the screw length is 100 mm, and the rubber gasket 4 is a circular rubber sheet with a diameter of 60 mm, which is convenient for combination with the bolt. The number of holes required for installing the shear bolt 5 is not less than 25 per square meter, and the height of the bolt end face from the wall surface must be greater than 10 mm.

[0064] (5) Continue spraying the second layer of ECC material to form a second ECC concrete layer 6 with a thickness of 15 mm, and perform surface treatment to obtain a reinforced structure.

[0065] Test example: In the embodiment of the present invention, expanded vitrified microspheres are used to replace the existing fine aggregate. After testing, it is found that when the replacement rate of the expanded vitrified microspheres is about 50% by volume, the performance of the ECC material is relatively superior. Therefore, in the embodiment of the present invention, an expanded vitrified microsphere with a volume replacement rate of 40%-60% is used, and the polyvinyl alcohol fiber content is selected to be 1%-3% by volume.

[0066] For the determination of the influence of the replacement rate of expanded glass microspheres on the performance of ECC materials, the test provided in the embodiment of the present invention selects ten mix ratios for comparison according to the scheme provided in the above embodiment 1, which are 0%, 25%, 50%, 75%, and 100% replacement rates of expanded glass microspheres at 2% polyvinyl alcohol fiber dosage and 1.5% polyvinyl alcohol fiber dosage, respectively. The test items are respectively carried out from three perspectives: compressive performance, splitting tensile performance, and thermal insulation performance (thermal conductivity coefficient). The following are the test methods and results:

[0067] 1. According to the above ratio, the ECC material is made into a cubic test block and subjected to a compression test, as follows:

[0068] According to the "Concrete Physical and Mechanical Properties Test Method Standard GB / T50081-2019"; the specimen size is a cubic specimen of 100mm*100mm*100mm, 3 pieces in a group; before the test, ensure that the specimen is clean and flat, and the dimensional error does not exceed 2%. Before the test, use a steel ruler to measure the actual size, and use an electronic scale to record the actual mass of the specimen.

[0069] After the specimen is formed, it should be placed in a room with a temperature of 20℃±5℃ and a relative humidity greater than 50% for 1d-2d. The specimen should be protected from vibration and impact during the standing period. After standing, it should be numbered, marked and demolded.

[0070] After the specimen is demoulded, it should be immediately placed in a standard curing room with a temperature of 20℃±2℃ and a relative humidity of more than 95% for curing; during the test, the load should be applied continuously and evenly, and the loading speed should be 0.3MPa / s~1.0MPa / s.

[0071] The compressive strength of the concrete cube specimen is calculated as follows: cc =F / A;

[0072] Where: f cc is the compressive strength of the cubic specimen (Mpa), and the calculation result should be accurate to 0.1MPa; F is the failure load of the cubic specimen (N); A is the pressure-bearing area of ​​the cubic specimen (mm).

[0073] The above test results are as follows Figure 4 As shown, the results show that at 2% fiber content, the change in the volume content of expanded glass beads has a relatively stable effect on the strength of the test specimens. At 0% to 100% expansion glass bead replacement rate, the test can achieve a compressive strength of more than 30 MPa. At the same time, at 50% glass bead replacement rate, the compressive performance of the two fiber content has a small loss and a higher strength.

[0074] 2. According to the above ratio, the ECC material is made into a cubic test block and a splitting tensile test is carried out, as follows:

[0075] According to the "Concrete Physical and Mechanical Properties Test Method Standard GB / T50081-2019"; the specimen size is a cubic specimen of 100mm*100mm*100mm, 3 pieces in a group; the production and maintenance are the same as the production of cubic compression test specimens.

[0076] During the test, the load should be applied continuously and evenly, with a loading speed of 0.05MPa / s-0.08MPa / s.

[0077] The tensile splitting strength of concrete cube specimen is calculated as follows: ts =2F / πA;

[0078] Where: f ts is the splitting tensile strength of the cubic specimen (Mpa), and the calculated result is accurate to 0.1MPa; F is the failure load of the cubic specimen (N); A is the splitting surface area of ​​the cubic specimen (mm).

[0079] The splitting tensile strength value measured using a non-standard specimen of 100mm*100mm*100mm should be multiplied by the size conversion factor of 0.85.

[0080] The above test results are as follows Figure 5 As shown, the results show that at 2% fiber content, the change in the volume content of expanded glass beads has a relatively stable effect on the splitting tensile strength of the test specimens. At the same time, the splitting tensile strength at 2% fiber content is significantly higher than that of the specimens at 1.5% fiber content. At the expansion glass bead replacement rate of 25% to 100%, the splitting tensile properties of the two fiber content changes relatively stably. Therefore, combined with the compressive performance test data, the mix ratio of 2% fiber content and 1.5% fiber content with 50% expansion glass bead replacement rate can be considered as the material basis for subsequent reinforcement work.

[0081] 3. According to the above ratio combination, the ECC material is made into test pieces, and the thermal insulation performance (thermal conductivity coefficient) test is carried out, as follows:

[0082] According to "Determination of Steady-State Thermal Resistance and Related Properties of Insulating Materials - Protective Heat Plate GB / T10294-2008", the specimen size is 300mm*300mm*30mm. The specimen is taken out from the standard curing room after 28 days to ensure that the surface is flat. It is baked in a baking oven to constant weight and then placed in a desiccator to cool to room temperature.

[0083] This test was commissioned by Jilin Province Construction Engineering Quality Inspection Center. The test results are as follows Figure 6As shown in the figure; by testing the specimens with 1.5% fiber content, the results show that the substitution rate of expanded glass beads has little effect on the thermal insulation performance of the specimens, but when the substitution rate is 50%, the specimen has the best thermal insulation performance. The reason is that on the one hand, the number of specimens is small and the change pattern of the overall data is not obvious. On the other hand, the specimens have more or less fiber clumping in the preparation process, which causes errors in the test results. This phenomenon has an impact on both the compressive performance test and the splitting tensile test.

[0084] Taking the three test results into consideration, the increase in fiber content has a small improvement on the splitting tensile properties of the specimens. However, the agglomeration phenomenon of 2% fiber content during the preparation process is more obvious than that of 1.5% fiber content, which is not only not conducive to the actual preparation operation, but also has a more obvious impact on the error of the test data. Therefore, the mix ratio of 50% glass bead replacement rate at 1.5% fiber content can be preferred as the material basis for subsequent reinforcement work.

[0085] Based on the above-mentioned ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above-mentioned description. The technical scope of the present invention is not limited to the contents of the specification.

Claims

1. A reinforcement process based on ECC material, characterized in that: The following steps are involved: After pre-treatment of the surface of the building to be reinforced, a first layer of ECC material is sprayed to form a first ECC concrete layer; the ECC material at least includes expanded vitrified microspheres as fine aggregate; Lay a fiber mesh cloth on the surface of the first ECC concrete layer, and press the fiber mesh cloth evenly into the surface layer of the first ECC concrete layer; On the surface of the fiber mesh cloth, shear studs with rubber gaskets are hammered to a specified depth so that the shear studs pass through the first ECC concrete layer and enter the interior of the building to be reinforced; Continue to spray the second layer of ECC material to form the second ECC concrete layer, and then perform plastering treatment.

2. The reinforcement process based on ECC material according to claim 1, characterized in that: The ECC material includes the following components: Portland cement 550-650 kg / m 3 、Fly ash 650-750kg / m 3 , fine aggregate 320-420kg / m 3 , Polycarboxylic acid high efficiency water reducing agent 2-6kg / m 3 , water 300-400kg / m 3 , and mixed with polyvinyl alcohol fiber; the fine aggregate includes quartz sand and expanded vitrified microspheres.

3. The reinforcement process based on ECC material according to claim 2, characterized in that: The volume content of the polyvinyl alcohol fiber is 1%-3%.

4. The reinforcement process based on ECC material according to claim 2, characterized in that: The particle size of the quartz sand is 40-80 meshes; the particle size of the expanded vitrified microspheres is 50-70 meshes.

5. The reinforcement process based on ECC material according to claim 4, characterized in that: In the fine aggregate, the volume proportion of the expanded vitrified microspheres is 40%-60%.

6. The reinforcement process based on ECC material according to claim 1, characterized in that: The fiber mesh cloth is a basalt fiber woven mesh.

7. The reinforcement process based on ECC material according to claim 1, characterized in that: The thickness of the first ECC concrete layer is 8-12 mm.

8. The reinforcement process based on ECC material according to claim 1, characterized in that: The thickness of the second ECC concrete layer is 10-15 mm.

9. A reinforced structure obtained by the reinforcement process based on ECC material according to any one of claims 1 to 8.

10. A building comprising the reinforced structure according to claim 9.